Textbook of Ocular Trauma Evaluation and Treatment - Kaufman, Stephen C.; Lazzaro, Douglas R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Arranged by ocular anatomy and subspecialty, with a detailed index permitting the reader to locate a discussion involving a specific type of ocular injury, this text covers ocular trauma in the pediatric and adult patient with medical and surgical treatment options, as well as potential complications. The Textbook of Ocular Trauma: Evaluation and Treatment provides a practical reference and educational resource for ophthalmologists, ophthalmology residents, emergency room physicians and residents, and pediatric physicians and residents, with basic and advanced instruction in the evaluation and management of eye and surrounding tissue trauma. This text includes multiple case reports with high quality color photographs after each section, as well as detailed medical illustrations of trauma cases and their treatment. Case studies include both common and unusual types of ocular and surrounding tissue trauma, which provide practical guidance in the evaluation and treatment of eye injuries.
Chapter 1. The Ocular Trauma Patient Encounter -- Chapter 2. Corneal Trauma -- Chapter 3. Trauma to the Anterior Chamber and Lens -- Chapter 4. Post-Refractive Surgery Trauma -- Chapter 5. Glaucoma Considerations -- Chapter 6. Eyelids -- Chapter 7. The Lacrimal System -- Chapter 8. Enucleation -- Chapter 9. Orbit -- Chapter 10. Retina and Posterior Segment Injuries -- Chapter 11. Sympathetic Ophthalmia -- Chapter 12. Optic Nerve, Visual Pathways and Oculomotor System -- Chapter 13. Pediatric Ocular Trauma -- Chapter 14. European Perspective of Ocular Trauma Management: Diagnostic and Therapeutic Considerations Based on Our Experience.
Keywords: Medicine; Emergency medicine; Critical care medicine; Ophthalmology; Medicine & Public Health; Ophthalmology; Emergency medicine; Intensive / Critical Care Medicine